2008
DOI: 10.1080/01612840701748664
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Seeking Help and Treatment Suggestions for Prenatal Depressive Symptoms: Focus Groups with Rural Low-Income Women

Abstract: Interviews were conducted with 21 pregnant or recently pregnant African American and Caucasian low-income women living in a rural southeastern community to elicit perceived barriers to seeking help for depressive symptoms in pregnancy and ways to overcome these barriers, as well as intervention suggestions. Participants identified themes regarding barriers to seeking help. These were: (1) lack of trust, (2) judgment/stigma, (3) dissatisfaction with the health care system, and (4) not wanting help. Themes ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 25 publications
4
106
1
3
Order By: Relevance
“…Dissatisfaction with and lack of trust in the health care system also have been reported as barriers to treatment (Jesse, Dolbier, & Blanchard, 2008).…”
mentioning
confidence: 99%
“…Dissatisfaction with and lack of trust in the health care system also have been reported as barriers to treatment (Jesse, Dolbier, & Blanchard, 2008).…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31] On contrary, few studies found that rural residence might be associated with high stress. 32,33 Yet other studies found no significant relationship between depression and place of residence. 30,34 The cause for low stress in rural women according to the authors might be due to the fact that, people in rural communities are more likely than their urban counterparts to live in joint family structure, which will provide necessary support to the female in this vulnerable state.…”
Section: Discussionmentioning
confidence: 76%
“…Jesse and Swanson (2007) found that rural pregnant women at risk for antepartum depression were almost four times more likely to experience negative stress than those at no risk for depression. However, this may be an underestimation, as pregnant women living in rural areas may not reveal their feelings of sadness and depression to professionals or to family, for fear of being labeled "crazy" or being reported to social services as unfit mothers (Jesse, Dolbier, & Blanchard, 2008). Lack of access to adequate mental health resources and transportation problems also prevent them from seeking medical treatment until late stages of a depressive episode, when symptoms are worse and effective intervention is more difficult (Bloom et al, 2012;Jesse et al, 2008).…”
Section: Relationships Of Stress Social Support and Self-esteem To mentioning
confidence: 98%